Florística e fitossociologia das espécies lenhosas no cerrado da fazenda Canchim (São Carlos, SP) - Tartaglia, Diego (Universidade Federal de São Carlos, 2004)
The situation of the remaining cerrado areas in Brazil is worrisome, and more studies are necessary to establish effective conservation strategies. We studied several aspects of the Woody species in two campo cerrado areas in order to assess the conditions of the vegetation. We placed five permanent 10 x 10 m plots in each area, in which we sampled the woody species in both the upper and lower strata and in the dry and wet seasons. We analyzed floristics, structure, β diversity, regeneration, seasonality and phenology. We did not find significant differences between the two areas in any of the descriptors, and therefore concluded that the β diversity was low. The upper stratum had a higher diversity and evenness than the lower, and was also more stable than the lower in relation to height structure throughout the year. We found no correlation between aggregation patterns and strata, area or season, and most species showed an aggregated pattern of distribution. The logarithmic series model was the better fit for both areas and layers, which predict a large proportion of low-density species. This has implications to the conservation strategies, because these species require large areas to maintain local populations without the risk of extinction. The flowering patterns were different between the strata, and a niche separation could be occurring. None of the species had regeneration problems. We considered that the area assure the reposition of the adult individuals of woody species.
Floristics and phytosociology of woody species in a campo cerrado vegetation at Canchim farm (southeastern Brazil).
Keywords: Ecologia vegetal; Florística; Comunidades vegetais; Cerrado; Fenologia; Variação sazonal; Diversidade biológica; CIENCIAS BIOLOGICAS::ECOLOGIA